Constitutional Court vs. Judicial Power (purpose of a competential process) - Malpartida Castillo, Víctor (2011)
In comparative law, frictions between the Judiciary and the Constitutional Tribunal are not new. As Garcia Belaunde recalls they have existed since the 60’s in Italy, from where the name «Battle of the Courts» originated, because the maximum judicial body in said country is the Court of Cassation and the concentrated body for constitutional control is the Constitutional Tribunal. The aforementioned phenomenon is replicated in Spain and in Colombia, where the incident is known as a «train crash». In our country, to debate whether the Constitutional Tribunal is hierarchically superior to the Judiciary is to mention the scope of Article 201 of the Constitution in force that defines the Constitutional Tribunal as the autonomous and independent «controlling body of the Constitution». However and strictly in relation to the foregoing, this article also tackles the binding precedent, a figure that was introduced in Article VII of the Preliminary Title of the Constitutional Procedural Code and that the Constitutional Tribunal, in its Judgment No 0024-2003-A1/TC, defined as «it is a legal rule in a specific and particular case which the Constitutional Tribunal decides to establish as a general rule», thereby becoming a normative parameter for the resolution of future similar proceedings. In consequence, due to its very condition, the constitutional precedent has similar effects to those of a law. In other words, «the general rule established as a precedent based on a specific case becomes a common precept for all defendants which is effective against the public powers». Finally, it proposes a reflection of the constitutional res judicata.